The first fossil avian egg from Brazil - Marsola, Julio Cesar de A.; Grellet-Tinner, Gerald; Montefeltro, Felipe C. [UNESP]; Sayao, Juliana M.; Hsiou, Annie Schmaltz; Langer, Max C. (Taylor & Francis Ltd, 2014)
Marsola, J.C.A., Grellet-Tinner, G., Montefeltro, F.C., SayAo, J.M., Hsiou, A.S. & Langer, M.C., 2014. The first fossil avian egg from Brazil. Alcheringa 38, 563-567. ISSN 0311-5518.In contrast to the rich record of eggs from non-avian dinosaurs, complete eggs attributable to Mesozoic birds are relatively scarce. Nevertheless, several well-preserved specimens have been discovered over the last three decades revealing functional and phylogenetic characters that shed light on the breeding strategies of extinct birds. Here we report the first fossil avian egg from Brazil, which was discovered in Upper Cretaceous strata of SAo Paulo in the southeastern part of the country. The taxonomic identity and structural features of the biomineralized tissues were determined using a combination of Scanning Electron Microscopy, Wave Dispersion Energy analyses and Computed Tomography. These show that the 125.5-m-thick shell of the 31.4x19.5mm egg incorporates three structural layers of similar thickness with both prismatic and aprismatic boundaries. Close similarity between the Brazilian bird egg and those of enantiornithines from the Upper Cretaceous Bajo de la Carpa Formation (Rio Colorado Subgroup) of Argentina advocates affinity with basal Ornithothoraces. Furthermore, coherency of their depositional contexts might imply a compatible preference for breeding and nesting environments.
Keywords: Upper Cretaceous; Vale do Rio do Peixe Formation; bird fossil eggs; Ornithothoraces; SAo Paulo